Exceptional remission in laryngeal synovial sarcoma: a unique case treated with single-modality IMRT- Ranchi tertiary care centre experience - Sharma, Satish; Kumari, Anamika; Kadapathri, Abhimanyu; Alam, Aftab; Singh, Priyanka; Tiwari, Vijay (International Journal of Research in Medical Sciences, 2025)
Laryngeal synovial sarcoma is an extremely rare cancer originating from smooth muscle cells predominantly found in the extremities. It is uncommon in the head and neck, with laryngeal involvement particularly rare, making accurate diagnosis challenging. This case report follows the journey of a 32-year-old female patient diagnosed with laryngeal synovial sarcoma. Notably, the patient underwent an unconventional treatment using only intensity-modulated radiation therapy (IMRT). Surprisingly, the patient achieved complete remission at the one-year follow-up, making this case exceptionally rare. It is noteworthy as one of the few instances where a single treatment modality, specifically IMRT, successfully led to complete remission in laryngeal synovial sarcoma treatment.